PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA PERUSAHAAN: PEMBELAJARAN ORGANISASI DAN INOVASI SEBAGAI VARIABEL INTERVENING (STUDI PADA BANK PERKREDITAN RAKYAT (BPR) KOTA PEKANBARU) - Ningrum, Indah Sawitri; Sari, Ria Nelly; Susilatri, Susilatri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The research aims to determine the effect of management control systems on firm performance mediated by organizational learning and innovation. This research uses sampling census method. The population in this study is the existing Rural Credit Bank which is represented by middle managers and top managers at each existing Rural Bank. The data collection technique used is by distributing questionnaires. Data analysis technique using Structural Equation Modeling-Partial Least Square (SEM-PLS) with Warppls version 5. The result of hypothesis testing in this research indicates that 1) management control system influence to firm performance, 2) management control system influence to organizational learning , 3) organizational learning has an effect on to innovation, 4) innovation influence to firm performance, 5) management control system which mediated by innovation has no effect to firm performance, 6) management control system mediated by organizational and innovation learning have positive and significant effect to firm performance.